2019
DOI: 10.1038/s41598-019-46327-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p23-1 cochaperone by protein kinase CK2 affects root development in Arabidopsis

Abstract: Root growth is a fundamental process in plants and assures nutrient and water uptake required for efficient photosynthesis and metabolism. Postembryonic development of roots is controlled by the functionality of the meristem. Several hormones and signaling molecules regulate the size of the meristem, and among them, auxins play a major role. Protein kinase CK2, along with the chaperone protein HSP90, has been found to be involved in the regulation of auxin transport. Here, we show that p23-1, a cochaperone of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Conversely, ARF5 is enriched in the cortex, expression of this gene in the cortex can drive cortical cell division 51 . At the same time, we found the cochaperone P23-1 enriched in cortex, where it has been reported to be crucial for auxin distribution and proper number of cortical cells 52,53 . Finally, we found the proteasome 19S regulatory particle 8a (RPN8a) enriched in cortical cells, here it interacts and induces the degradation of BRAHMA to promote boron tolerance 54 .…”
Section: Resultssupporting
confidence: 52%
“…Conversely, ARF5 is enriched in the cortex, expression of this gene in the cortex can drive cortical cell division 51 . At the same time, we found the cochaperone P23-1 enriched in cortex, where it has been reported to be crucial for auxin distribution and proper number of cortical cells 52,53 . Finally, we found the proteasome 19S regulatory particle 8a (RPN8a) enriched in cortical cells, here it interacts and induces the degradation of BRAHMA to promote boron tolerance 54 .…”
Section: Resultssupporting
confidence: 52%
“…Root length, root number, root growth in Arabidopsis, rice, and soybean; nutrient stress tolerance [63][64][65][66][67] GH3 family, GH3 auxin-responsive promoter…”
Section: Putative Candidate Genes Controlling Wheat Root Traitsmentioning
confidence: 99%
“…TraesCS7A02G431500 identified in pairs 9-10 encode protein kinase. Alpha4 (α4) subunit of casein kinase 2, CK2 α4, a protein kinase regulated primary root elongation, lateral root formation, and root development in Arabidopsis [63,66]. Overexpression of stress/ABA-activated protein kinase 10 (SAPK10) in transgenic rice produced longer root hairs than the wild type [71].…”
Section: Traescs7a02g101000mentioning
confidence: 99%
“…In addition to being involved in steroid receptors, p23 has been found to be associated via Hsp90 with several other proteins, including transcription factors, protein kinases, viral proteins, and mature client structures (Echtenkamp et al, 2016 ; Hu et al, 1997 ; Nair et al, 1996 ; Xu et al, 1997 ). Moreover, recent studies have observed that p23 can associate independently with proteins and have additional functions of enzyme activity and more of independent of chaperoning (D'Alessandro et al, 2019 ; Felts & Toft, 2003 ). The presence of p23 is ubiquitous and highly conserved from yeast to humans (Garcia‐Ranea et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%